The Athens Affair. - Prevelakis, V.
How some extremely smart hackers pulled off the most audacious cell-network break-in ever. On 9 march 2005, a 38-year-old Greek electrical engineer named Costas Tsalikidis was found hanged in his Athens loft apartment, an apparent suicide. It would prove to be merely the first public news of a scandal that would roil Greece for months. The next day, the prime minister of Greece was told that his cellphone was being bugged, as were those of the mayor of Athens and at least 100 other high-ranking dignitaries, including an employee of the U.S. embassy. The victims were customers of Athens based Vodafone-Panafon, generally known as Vodafone Greece, the country's largest cellular service provider. Tsalikidis was in charge of network planning at the company. A connection seemed obvious. Given the list of people and their positions at the time of the tapping, we can only imagine the sensitive political and diplomatic discussions, high-stakes business deals, or even marital indiscretions that may have been routinely overheard and, quite possibly, recorded. Even before Tsalikidis's death, investigators had found rogue software installed on the Vodafone Greece phone network by parties unknown. Some extraordinarily knowledgeable people either penetrated the network from outside or subverted it from within, aided by an agent or mole. In either case, the software at the heart of the phone system, investigators later discovered, was reprogrammed with a finesse and sophistication rarely seen before or since. A study of the Athens affair, surely the most bizarre and embarrassing scandal ever to engulf a major cellphone service provider, sheds considerable light on the measures networks can and should take to reduce their vulnerability to hackers and moles. It's also a rare opportunity to get a glimpse of one of the most elusive of cybercrimes. Major network penetrations of any kind are exceedingly uncommon. They are hard to pull off, and equally hard to investigate.
Keywords: Athens; Greece; Vodafone-Panafon.; Cell-network break-in.; Cellphone bugging; Cellular service provider; Cybercrime; Hacking; Network penetration